Correlación entre potencia y resistencia en jugadores de fútbol de Boyacá (2019)
The research aimed to determine the correlation between power and resistance at speed in the players category sub - 17 of the professional football team Patriots Boyaca.f.c, which used a methodology with a focus empirical analytical descriptive correlational design, the study sample was constituted by 18 players with average age of 16.40 years, average weight of 68 kg and average size of 1.72 meters, which applied the test of Bosco jumps thread (ABK) Counter movement Jump (CMJ) and Squat Jump (SJ) being evaluated with the platform contact Axon Jump 4.0 and the test Repeat Sprint Ability (RSA), in order to analyze the study variables. The statistical analysis of the data was used for the statistical package SPSS v.22.0 (IBM Company Chicago), yielding results in the show that correlation there is no between indicators of the RSA and ABK and SJ, jumps while the anti movement CMJ presents correlation with the fatigue rate power and best sprint (P = 0, 03) (P = 0, 02) (P = 0, 05) respectively. Carrying out the Pearson r correlation coefficient parametric data and a greater than or equal to 0.05 Alpha